Synchronous flowering despite differences in snowmelt timing among habitats of Empetrum hermaphroditum - Bienau, M.J.; Kröncke, M.; Eiserhardt, W.L.; Otte, A.; Graae, B.J.; Hagen, D.; Milbau, A.; Durka, Walter; Eckstein, R.L. (Acta Oecologica, 2015)
The topography within arctic-alpine landscapes is very heterogeneous, resulting in diverse snow distribution patterns, with different snowmelt timing in spring. This may influence the phenological development of arctic and alpine plant species and asynchronous flowering may promote adaptation of plants to their local environments.We studied how flowering phenology of the dominant dwarf shrub Empetrum hermaphroditum varied among three habitats (exposed ridges, sheltered depressions and birch forest) differing in winter snow depth and thus snowmelt timing in spring, and whether the observed patterns were consistent across three different study areas.Despite significant differences in snowmelt timing between habitats, full flowering of E. hermaphroditum was nearly synchronous between the habitats, and implies a high flowering overlap. Our data show that exposed ridges, which had a long lag phase between snowmelt and flowering, experienced different temperature and light conditions than the two late melting habitats between snowmelt and flowering.Our study demonstrates that small scale variation seems matter less to flowering of Empetrum than interannual differences in snowmelt timing.